Evaluation of network security based on next generation intrusion prevention system - Gilang Intan Permatasari Duppa; Nico Surantha (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Next Generation Intrusion Prevention System (NGIPS) is a system that works to monitor network traffic, to detect suspicious activity, and to conduct early prevention toward intrusion that can cause network does not run as it supposed to be, NGIPS provides vulnerability protection broader compared to the traditional IPS, especially in the application layer that has ability to detect and learn vulnerability asset and carried out layering inspection until layer 7 packet. This paper intended to analyze and evaluate the NGIPS to protect network from penetration system that utilize the weakness from firewall, that is exploitation to HTTP port. By the existence of NGIPS, it is expected can improve the network security, also network administrator could monitor and detect the threats rapidly. Research method includes scenario and topology penetration testing plan. The result of this research is the evaluation of penetration testing that utilizes HTTP port to exploit through malicious domain. The evaluation conducted to ensure the NGIPS system can secure the network environment through penetration testing. This study can be concluded that it can become reference to optimize network security with NGIPS as network security layer.